STRATEGI PENINGKATAN PENJUALAN PRODUK MELALUI PEMASARAN ONLINE PADA PEDAGANG SAYUR KELILING GRIYA BUKIT MAS BANDUNG - Fitriani, Efi (Lembaga Pengabdian Masyarakat Universitas Swadaya Gunung Jati, 2021)
This community service program aims to give training about the strategy methods to increase product sales through online marketing to vegetable traders around Bandung. The problems are declining sales turnover, not knowing the mechanism for using applications for online marketing, not being able to promote products through social media. The solution offered was to provide directions and procedures for strategies to increase product sales through online marketing through social media. The specific target is to promote on Facebook to increase product sales.The activities started by giving directions on how to use the Facebook social media application to promote their wares, finding out their consumers' mobile phone numbers so that partners can offer their wares. With the training provided by the team, the mobile vegetable seller, Mang Edo, is more developed with an increase in the number of consumers who buy his merchandise. There are many strategies that can be done, build customer loyalty, do online sell on social media, using Facebook so that they are more familiar and skilled, doing promotions on social media, expanding marketing area, trying to accept orders in other areas, do promote on Facebook to expand marketing area, increase shipping costs for remote areas.